Diagnostic and vaccine potential of Zika virus envelope protein (E) derivates produced in bacterial and insect cells - Lunardelli, Victória Alves Santos; Almeida, Bianca da Silva; Apostolico, Juliana de Souza; Rezende, Thais; Yamamoto, Marcio Massao; Pereira, Samuel Santos; Bueno, Maria Fernanda Campagnari; Pereira, Lennon Ramos; Carvalho, Karina Inacio; Slhessarenko, Renata Dezengrini; de Souza Ferreira, Luis Carlos; Boscardin, Silvia Beatriz; et al. (Frontiers in Immunology, 2023)
Introduction In the present study we evaluated the features of different recombinant forms of Zika virus (ZIKV) proteins produced in either bacterial (Eschericha coli) or insect cells (Drosophila melanogaster). The ZIKV-envelope glycoprotein (EZIKV) is responsible for virus entry into host cells, is the main target of neutralizing antibodies and has been used as a target antigen either for serological tests or for the development of subunit vaccines. The EZIKV is composed of three structural and functional domains (EDI, EDII, and EDIII), which share extensive sequence conservation with the corresponding counterparts expressed by other flaviviruses, particularly the different dengue virus (DENV) subtypes. Methods In this study, we carried out a systematic comparison of the antigenicity and immunogenicity of recombinant EZIKV, EDI/IIZIKV and EDIIIZIKV produced in E. coli BL21 and Drosophila S2 cells. For the antigenicity analysis we collected 88 serum samples from ZIKV-infected participants and 57 serum samples from DENV-infected. For immunogenicity, C57BL/6 mice were immunized with two doses of EZIKV, EDI/IIZIKV and EDIIIZIKV produced in E. coli BL21 and Drosophila S2 cells to evaluate humoral and cellular immune response. In addition, AG129 mice were immunized with EZIKV and then challenge with ZIKV. Results Testing of samples collected from ZIKV-infected and DENV-infected participants demonstrated that the EZIKV and EDIIIZIKV produced in BL21 cells presented better sensitivity and specificity compared to proteins produced in S2 cells. In vivo analyses were carried out with C57BL/6 mice and the results indicated that, despite similar immunogenicity, antigens produced in S2 cells, particularly EZIKV and EDIIIZIKV, induced higher ZIKV-neutralizing antibody levels in vaccinated mice. In addition, immunization with EZIKV expressed in S2 cells delayed the onset of symptoms and increased survival rates in immunocompromised mice. All recombinant antigens, either produced in bacteria or insect cells, induced antigen-specific CD4+ and CD8+ T cell responses. Conclusion In conclusion, the present study highlights the differences in antigenicity and immunogenicity of recombinant ZIKV antigens produced in two heterologous protein expression systems.